Tindak Pencemaran Nama Baik Yang Dilakukan Melalui Media Sosial Di Tengah-Tengah Masyarakat - Widitsani, Fiddar Bidawan; Apripari, Apripari; Kaluku, Julisa Aprilia (CV. ITTC INDONESIA, 2023)
Disparity is the difference in deciding one case with another, this is often a question in a society about how this disparity can occur, which is when there is one case that is the same, but the way of giving sanctions is different, this also causes a Indonesian law is questioned whether the sanctions or punishments are appropriate or not and whether justice exists or not. This distinction will also stem from how a decision has been made by a judge, which basically judges give punishment based on several aspects, and where judges also have authority to decide a case. The purpose of this research is to find out what disparity is, and how considerations and legal aspects are used to decide a case. In this case, there is a disparity that will be discussed regarding the Disparity in Judges' Decisions Against the Crime of Defamation on Social Media (Analysis of Decisions Number 755/Pid.Sus/2020/Pn.Gtlo and 331/Pid.Sus/2019/Pn Gtlo). Where the method used is qualitative research with a statutory approach, conceptual approach, and a comparative approach and this type of research is normative juridical research.